Associations of physical activity and screen time with adolescent idiopathic scoliosis - Liwan Zhu; Shouhang Ru; Wanxin Wang; Qiufen Dou; Yanzhi Li; Lan Guo; Xiaosheng Chen; Weijun Wang; Wenyan Li; Zhixiang Zhu; Lei Yang; Ciyong Lu; et al. (Environmental Health and Preventive Medicine, 2023)
Background: Adolescent idiopathic scoliosis (AIS) is the most common type of idiopathic scoliosis, affecting approximately 0.61%–6.15% adolescents worldwide. To date, the results on the relationship between moderate-to-vigorous physical activity (MVPA) and AIS were inconsistent, and the association between screen time (ST) and AIS remained unclear. This study aimed to describe MVPA and ST among adolescents, and to explore the independent and joint associations between PA, ST, and AIS. Methods: A frequency-matched case-control study based on the 2021 Chinese School-based Scoliosis Screening Program in Shenzhen city, south China, was conducted. The research involved 494 AIS patients (aged 9–17 years) and 994 sex- and age-matched healthy controls. MVPA and ST were measured using a self-administered questionnaire. Logistic regression models estimated associations between PA, ST, and AIS. Results: Compared to subjects meeting the recommended 60-min daily of MVPA, adolescents reporting daily MVPA time less than 60 min had 1.76 times higher odds of experiencing AIS (95% CI: 1.32–2.35) and adolescents reporting daily MVPA in inactive status had 2.14 times higher odds of experiencing AIS (95% CI: 1.51–3.03). Moreover, participants reporting ST for 2 hours or more had 3.40 times higher odds of AIS compared with those reporting ST less than 2 hours (95% CI: 2.35–4.93). When compared with the adolescents reporting both ST and MVPA meeting the guidelines recommended times (ST < 2 h and MVPA ≥ 60 min/day), those reporting both ST ≥ 2 h and MVPA in inactive status are 8.84 times more likely to develop AIS (95% CI: 3.99–19.61). Conclusions: This study reported that the insufficient MVPA, especially MVPA in inactive status, and excessive ST were risk factors for AIS. Additionally, the joint effects of insufficient MVPA and excessive ST probably increase the risk of AIS.